Pengaruh Gaya Kepemimpinan Perempuan Terhadap Organizational Citizenship Behavior (OCB) Guru di MAN 2 Langkat - Khofifah Riana Br Bangun; Ahmad Zaki; Pitriani Nasuion (Invention: Journal Research and Education Studies, 2026)
This study aims to examine the influence of female leadership style on teachers’ Organizational Citizenship Behavior (OCB) at MAN 2 Langkat. The research employed a quantitative approach using a survey method. The research instruments consisted of observation and questionnaires designed based on a Likert scale. The population of this study included all teachers at MAN 2 Langkat, totaling 70 individuals, who were simultaneously used as the research sample through a total sampling technique. Data analysis was conducted using descriptive and inferential statistics, including tests of normality, homogeneity, linearity, simple regression analysis, and the paired samples t-test. The results showed that the female leadership style of the madrasah principal was categorized as high, with a mean score of 89.22, while teachers’ OCB was also in the high category with a mean score of 90.19. The simple regression analysis indicated that female leadership style had a positive and significant effect on teachers’ OCB, with a regression coefficient of 0.992 and a significance value of 0.000 (p < 0.05). In addition, the correlation test results revealed a very strong relationship between the two variables, with a correlation coefficient of r = 0.996. Based on these findings, it can be concluded that female leadership style plays a very important role in encouraging teachers’ OCB, thereby creating a conducive, collaborative work climate oriented toward improving the quality of education at MAN 2 Langkat.